PEMBANGUN DAN PELIBATAN KELUARGA DALAM SIKLUS HIDUP SENI PERTUNJUKANPARIWISATA PADA TEATER BALI AGUNG TAMAN SAFARI AND MARINE PARK - I Putu Ardiyasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Family in an organization or business activity is often regarded as negative nepotism. However, in the performing arts culture industry, many organizations are built from the involvement of family members and have strong family ties. Therefore, many successful (sustainable) cultural industries are managed by families. The purpose of this empirical study is to investigate the two elements of human capital and structural capital that are thought to be the basis of building and involving families in the life cycle of the performing arts Tourism at the Bali Agung Theater Taman Safari and Marine Park, Gianyar, Bali. This empirical study uses qualitative methods with a case study approach. The results showed that the organization or assets of the organization must have the best quality of art that is supported by aggressive offers, as well as building families and spectators to be able to get financial benefits to support the sustainability of the organization or cultural institutions that are managed. Keywords: Life Cycle, Performing Arts Tourism, Families involvement